Diagnosis of sphincter of Oddi dysfunction in patients with postcholecystectomy syndrome from hepatobiliary scintigraphic findings - M. V. Repin; V. Yu. Mikryukov; T. E. Vagner; N. M. Pleshkova (Вестник рентгенологии и радиологии, 2016)
Objective: to diagnose and estimate the clinical value of postcholecystectomy sphincter of Oddi dysfunction in patients.Material and methods. Examinations were made in 100 postcholecystectomy patients without signs of cholestasis; of them 14 postpapillotomy patients formed a comparison group. Hepatobiliary scintigraphy using the radiotracer 99mTC-bromeside was performed for 90 minutes with cholagogue breakfast at 45 minutes. Common bile duct and duodenal functions and duodenogastric reflux (DGR) were evaluated comparing them with clinical, laboratory, and instrumental findings.Results. Two patient groups were identified according to bile outflow changes. In Group 1 consisting of 20 (23.2%) patients, the time of maximum accumulation (Tmax) of the radiopharmaceutical in the projection of the choledochus coincided with that in the cholagogue test (46.0±1.8 min) and in Group 2 including 66 (76.8%) patients that was shorter than in the cholagogue test (32.9±6.8 min) (p<0.05). In Group 2, Tmax was similar to that in the comparison group (30.9±7.5 min; р>0.05) and there was no significant difference in intestinal imaging time (18.6±6.0 min versus 17.6±0.8) either, which could be indicative of sphincter of Oddi dysfunction. Diarrhea was observed in 73% of the patients with sphincter of Oddi dysfunction and in 86% of the patients in the comparison group versus 10% of the patients with normal bile passage (p<0.01). Statistical data processing showed a correlation of the indicators of sphincter of Oddi dysfunction with those of duodenal evacuator function (r=0.57; p<0.0005) and DGR (r=0.74; p<0.009).Conclusion. Postcholecystectomy sphincter of Oddi dysfunction assumes the greatest clinical value in patients with duodenal motor-evacuator dysfunction, which should be kept in mind when choosing a treatment policy.